2020
DOI: 10.1051/0004-6361/202038010
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the raw contrast of VLT/SPHERE with the dark hole technique

Abstract: Context. Since 1995 and the first discovery of an exoplanet orbiting a main-sequence star, 4000 exoplanets have been discovered using several techniques. However, only a few of these exoplanets were detected through direct imaging. Indeed, the imaging of circumstellar environments requires high-contrast imaging facilities and accurate control of wavefront aberrations. Ground-based planet imagers such as VLT/SPHERE or Gemini/GPI have already demonstrated great performance. However, their limit of detection is h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…The ratio of the integration time and the coherence time will determine how strong the incoherent background will be. With the focal-plane feedback, the contrast in the dark hole will be limited to the incoherent background (Galicher et al 2019;Singh et al 2019;Potier et al 2020). The exact effect that the residual turbulence will have on the SM-SCC will be part of a later work.…”
Section: One-sided Dark Hole Wavefront Controlmentioning
confidence: 96%
See 1 more Smart Citation
“…The ratio of the integration time and the coherence time will determine how strong the incoherent background will be. With the focal-plane feedback, the contrast in the dark hole will be limited to the incoherent background (Galicher et al 2019;Singh et al 2019;Potier et al 2020). The exact effect that the residual turbulence will have on the SM-SCC will be part of a later work.…”
Section: One-sided Dark Hole Wavefront Controlmentioning
confidence: 96%
“…In most cases, before the one-sided dark hole was created, the Strehl was increased by applying multiple steps of feedback with the full dark hole (Potier et al 2020). This step was used to increase the Strehl of the system.…”
Section: One-sided Dark Hole Wavefront Controlmentioning
confidence: 99%
“…Finally, there myst be a choice of optimal wavefront state: the goal of the AO system may not always be to produce a flat wavefront. For example, in a HCI, cancellation of static diffraction features (airy diffraction rings, telescope spiders), such as dark hole techniques (Potier et al 2020), may be aimed at driving the AO loop to a non-flat wavefront state.…”
Section: Introductionmentioning
confidence: 99%
“…In the particular case of NCPAs, these images are ideally generated by the science detector. Several solutions have been suggested for static NCPAs (Paxman & Fienup 1988;Frazin 2018;Vigan et al 2018;Vievard et al 2020;Bos et al 2020;Potier et al 2020;? ), the quasi-static part is shown to be particularly challenging to measure and correct.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have also been applied to compensate for noncommon path aberrations in ground-based AO systems. 12 The Coronagraph Instrument (CGI) on the upcoming Roman Space Telescope, formerly known as WFIRST, will demonstrate these methods in flight for the first time. 13,14 The HabEx and LUVOIR telescope concepts are specifically designed to be ultra-stable in order to accommodate the direct imaging of Earth-like exoplanets with their respective coronagraph instruments.…”
Section: Introductionmentioning
confidence: 99%